The collapsing empire - Scalzi, John, 1969- (Scalzi, John, 1969- Interdependency, 2017)
Faster than light travel is impossible--until the discovery of The Flow, an extradimensional field available at certain points in space-time, which can take us to other planets around other stars. Riding The Flow, humanity spreads to innumerable other worlds. Earth is forgotten. A new empire arises, the Interdependency, based on the doctrine that no one human outpost can survive without the others. It's a hedge against interstellar war--and, for the empire's rulers, a system of control. But when it's discovered that the entire Flow is moving, possibly separating all human worlds from one another forever, a scientist, a starship captain, and the emperor of the Interdependency must race to find out what can be salvaged from an empire on the brink of collapse. --